Analytical and Comparative Study of Job Satisfaction for Olympic Sport Federation referees Of Both Individual Sport and Team sports - Jasim, Moaid (Journal of Physical Education, 2016)
Research indicates the importance of meeting the needs of the functional and personal for referees, and providing public services to them by sports organization.The research problem can be summarized in two questions: What is the level of job satisfaction among the referees? And what are the similarities and differences in job satisfaction when comparing the referees working in the individual and team federations?The researchers used the descriptive analytical method and style comparisons. The study population consisted of (1117) referees. Distributed on (22) sports federations of the Olympic individual sport and team sport.The researchers concluded that the level of job satisfaction among referees working in the individual and team federations were low on a general level, there are differences in the level of job satisfaction between the two samples and in favor of the referees working in the team sports federations.The researchers recommended emphasizing on the importance of providing good financial income for referees.